Aias Mastigophoros - Inkret, Andreja (Clotho, 2019)
The paper analyses a short scene that forms part of the opening of Sophocles' Aias (66-133): Aias, suffering from the madness that was inflicted upon him by Athena, is displayed by the goddess to Odysseus. In the corpus of extant ancient drama, this inset appears to be unique. Its expressive power is derived from the scene's specific structure that doubles the integral elements of theatre. The paper suggests the reasons why the scene has often been labelled "a play-within-a-play," describing and illustrating the elements that can be paralleled with the structural components of theatre. Taking as basis concepts and ideas proposed by modern theatre theoreticians (Anne Ubersfeld, Tadeusz Kowzan, Umberto Eco), the paper argues that the essence of the performative dimension of the scene is to be found in the phenomenon of the "ostentation act" first described by Umberto Eco. Tracing the meaning of the inset within the tragedy as a whole, the paper emphasizes the fact that the "ostentation" in Aias is a divine creation, and examines how Odysseus, a privileged recipient of the spectacle, reacts to the display of Aias' shameful condition.
Keywords: grška dramatika; igra v igri; razkazovanje; Sophocles; teorija gledališča